Efektivitas Teknologi E-Learning Dalam Pembelajaran Bahasa Arab di Kelas Bahasa MAN 2 Kota Serang, Banten - Nuraman (EL-TA’DIB: Journal of Islamic Education, 2025)
This study aims to analyze and test the effectiveness of Arabic language learning results with the application of e-learning technology in class XI Language MAN 2 Serang City, Banten. This research is a type of field research and this research uses a mix method research methodology and a concurrent embedded strategy model design. Data sources were taken through pre-test and post test questions, questionnaires, observations, interviews, and documentation as well as from relevant literature that supported this research. The location of the research is in Class XI Language MAN 2 Serang City. The data analysis of this study uses methodoligical triangulation, which is a combination of quantitative methods and qualitative methods in a single case. The results of the findings in the field show that the application of e-learning technology in Arabic learning is more effective, more innovative and fun than conventional learning media. The application of e-learning technology attracts more students' attention and makes it easier for students to understand Arabic materials. There is a significant difference in results between Arabic learning and e-learning technology \ compared to conventional learning media. Keywords: E-learning, Electronics, Arabic, Madrasah